THE STRENGTHENING ROLE OF ISLAMIC FINANCIAL INSTITUTIONS FOR THE REAL SECTOR OF SMEs - Tri Mulato; Nursyamsu Nursyamsu (Jurnal Iqtisaduna, 2019)
The concept of Islamic economics that prioritizes for optimization of the real sector and makes the financial sector as driving factor of economic activity. Islamic financial institutions continue to provide services for working capital, especially for SMEs, reaching 5 percent. The SMEs also continue to grow to 10 percent, becoming an opportunity for Islamic financial institutions to be able to accompany the movement of SMEs. This article is descriptive qualitative. Described the development of shariah banking financing product  for SMEs and the important role of Islamic financial institutions for SMEs. The results of the study show that the distribution of Islamic bank financing for SMEs in the period of December 2016 to September 2017 reached 61,299,000,000 or grew by 5.504 percent. The biggest financing for SMEs on BUS is equal to 44,872,000, the largest growth in UUS is 21,339 percent. The concept of Islamic economics has similarities with the economic concept of SMEs, both of which are resistant to the storm of crisis, then the concept of Islamic economics puts forward the distribution of income, through Islamic financial institutions income distribution can be realized. Islamic financial institutions will continue to contribute to economic development especially for the SMEs real sector.